Complete guide to debt recovery - Mason, Roger (Thorogood, 2003)
This work guides the reader through every stage of debt recovery, from deciding to take action to serving a claim and the trial itself. It deals comprehensively with enforcing judgement and features sections on bankruptcy, winding up receivership and administration.